The effectiveness of ginger and mint leaves decoction toward the frequency of emesis gravidarum - Rochkmana, Meika Jaya; Widyawati, Melyana Nurul (Poltekkes Kemenkes Yogyakarta, 2018)
The pregnancy causes physical, psychological and hormonal changes of the mother. This is can cause a variety of trouble or complaints, and one of them is nausea and vomiting. Although, the emesis gravidarum is considered normal for first trimester pregnant if the frequency of nausea is excessive vomiting must be aware. Emesisgravidarum in early pregnancy can be reduced by non-pharmacological approaches including herbs such as ginger, mint, chamomile, acupuncture, and massage. The research method used is Quasy Experiment Design with Time Series Design. The study was carried out at Kesesi I Primary Health Care in Pekalongan Central Java 2018. The sampling using Purposive sampling and obtained as many as 30 respondents. The statistical test used is the Mann Whitney Test. The results of this study showed that administration before and after ginger decoction in pregnant women reduced the frequency of emesis gravidarum with an average difference of 2,333 with p-value 0,000 <α (0,05). In the mint leaf group, the mean difference was 1,200 with p-value 0,000 <α (0,05). This shows that both the ginger stew and mint leaves have an effect on decreasing the frequency of emesis gravidarum in pregnant women. For efficacy results obtained the decoction of ginger with a mean rank of 20.87 compared with the group of mint leaves decoction of 10.13 so it can be concluded that the ginger stew is more effective than mint leaves.